Kunci Literasi: Jangan Paksa Anak Membaca? - Febiyanti, Nabila; Asbari, Masduki; Lestari, Silvi; Santoso, Gunawan (Yayasan Aya Sophia Indonesia, 2023)
The purpose of this study was to find out Nadiem Makarim's philosophical study from the Guru Dok TV Youtube channel entitled